Assessment, types, and etiologies of vision loss in primary care settings - Al Nahdi, Ahmed Thabit; Alobaid, Abdulaziz Ahmad; Alajmi, Abdullah Khalid; Al Majed, Abdullah Saleh; Alkhars, Ali Abdulhaq; Alsayyar, Manal Amer; Althani, Husain Amer; Almansour, Abdulaziz Jamal; Alsaadi, Khaled Ali; Aljaloud, Norah Abdullah; Alwabel, Saga Khaled (International Journal Of Community Medicine And Public Health, 2021)
Studies indicate the vital roles that family physicians play in the diagnosis and assessment of vision loss in the primary care settings. In ddition, family physicians give proper advice to patients and refer them to other departments for adequate screening and management of any associated comorbidities. In this literature review, we have discussed the types, etiologies, and assessment of each cause of vision loss in primary care settings. The most commonly reported etiologies include age-related macular degeneration (AMD), diabetic retinopathy, glaucomas, cataracts, and errors of refraction. The main types of vision loss usually include peripheral vision loss, central vision loss, blurred or patchy vision, and vision loss that is usually associated with a physical disability or an acquired brain injury. Providing adequate management and routine screening for the patients that are affected by the aforementioned etiologies can significantly enhance their outcomes and reduce the risk of vision loss. Providing educational campaigns about the importance of treatment compliance and routine screening should also be conducted to increase awareness and enhance the outcomes in the primary care settings.